PRODUCT QUALITY SUPERVISION MANAGEMENT AT DIKI CERAMICS (HOME INDUSTRY) WEDI DISTRICT, KLATEN REGENCY - Erna Chotidjah Suhatmi; Agus Suyatno; Ananda Nur Wahit (Proceeding of International Conference on Science, Health, And Technology, 2022)
Quality control is a series of effective and efficient integrated activities that develop, maintain and improve the quality of some products and services to make consumers satisfied. The current study aims to identify consumers opinions on product quality, quality management systems, and costs required for it. The research was conducted at the Diki Ceramic Home Industry. That Data analysis used control chart, cost analysis and qualitative descriptive. That The data used in this study are consumer perception data and the number of products produced, the number of defective products, and the costs required to support them control process for one period. The results of the study show that product quality is controlled as a proportional value of damage is between the upper and lower limits, indicating that the controlling limitis (p) = 14%, the upper control limit is (UCL) 16,68%, the lower control limit (LCL) is 11,31%. Total cost required to control process control (QCC) Rp 535,714,285 the cost needed to guarantee the quality is Rp. 10,500,000., and the cost of quality (TQS) of Rp. 546,214,285 means company can compress the product by 210 earthenware or 14% of the total production. Score optimum damage (q*) is 1500 of respondents indicated very positive perception, 50% indicate positive perception, and 6.67% indicate neutral perception.